Quality of the Work of Internal Audit - Samed Abdel Amir Said; Fatima Saleh Al Gharban (Journal of Madenat Alelem University College, 2020)
The internal audit system has an important position in the structure of economic units, The importance of this site comes from the importance of the role played by these devices as they represent the support body for the work of the administration through its advisory and advisory role and the guarantor to reduce the manipulation and waste of funds of economic unity as it represents an important stage of public money control. It is also a means of evaluating the effectiveness of operations and ensuring compliance with the standards. The research aims to identify mechanisms to enhance the quality of the work of the internal auditing bodies(Weaknesses in the work of the internal audit services and a severe shortage of internal auditors). The research concluded with a set of recommendations, the most important of which are (Confirmation of the adoption of mechanisms that achieve the quality of the work of the internal audit).